ANALISIS DAMPAK KENAIKAN HARGA KEDELAI TERHADAP PENDAPATAAN USAHA TAHU (Studi Kasus: Pengrajin Tahu Pak Sardi Desa Rajabasa Baru Kecamatan Mataram Baru Kabupaten Lampung Timur) - Buchori Buchori; Rika Rida Sari; Fauzi Fauzi (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2020)
This study aims to: Analyze the impact of the increase in soybean prices on the income received by Pak Sardi and to analyze the feasibility of Pak Sardi's tofu industry after the increase in soybean prices. The data used are secondary data, secondary data obtained from literature studies sourced from the annual report of the Mataram Baru District Office, the Central Statistics Agency, as well as the East Lampung City Trade and Industry Service. The results showed that it can be seen that the average income of Pak Sardi's tofu craftsmen before the increase in soybean prices was IDR 6,254,918.00 per 3 months, and after the increase in soybean prices was IDR 5,847,188.00 per 3 months. Based on the calculation of the average R / C ratio, it is known that the tofu craftsman business before the soybean price increase had an average R / C ratio of 2.21. This means that every expenditure of Rp. 1.00 will result in an average income of Rp. 2.21 so that the business of a tofu craftsman is feasible because the average value of R / C ratio is1.The tofu craftsman business after the increase in soybean prices is still feasible because of its the average R / C ratio is greater than one (average R / C ratio 1), which is IDR 2.13.